FORMULATION, QUALITY TEST, AND ANTIBACTERY ACTIVITY TEST OF LIQUID SOAP OF ACALIFA (Acalypha wilkensiana Müell. Arg.) LEAVES on Escherichia coli - Hilda Khoirunnisa Rohma; Lina Winarti; Nafisah Isnawati (International Journal of Islamic and Complementary Medicine, 2025)
Although antibacterial soaps have begun to be developed, using akalifa leaves as an active antibacterial ingredient in liquid soap has not been widely explored. Akalifa leaf extract ( Acalypha wilkensiana Müell. Arg. ) is a plant that has antibacterial activity against Escherichia coli bacteria. Escherichia coli bacteria are the most common cause of diarrhea and spread through dirty hands. One way to prevent diseases caused by bacteria is to use liquid soap made using the saponification process with or without adding other ingredients that do not irritate the skin of the hands. Objective: This study aimed to develop and utilize akalifa leaf extract ( Acalypha wilkensiana Müell. Arg. ) into liquid soap with various extract concentrations. This study was conducted experimentally in the laboratory. Akalifa leaf samples were extracted using the maceration method with 70% ethanol solvent, and the results of the khalifa leaf extract obtained were subjected to phytochemical screening tests. The amount of active substances used with variations in concentrations of FI (3%), F2 (6%) and F3 (9%). The resulting liquid soap preparation was evaluated physically, including organoleptic, homogeneity, pH, foam height, and viscosity. After that, the antibacterial activity test used the well method. The results of the study showed that khalifa leaf extract contains alkaloid, flavonoid, tannin, and saponin compounds. The results of the physical quality evaluation of the three akalifa leaf extract liquid soap formulations meet the range requirements permitted by SNI. The results of the antibacterial activity test showed that all formulations produced inhibition against Escherichia coli bacteria, with a concentration inhibition diameter of 3% (7.55mm ± 0.61) in the moderate category and a concentration of 6% (10.94mm ± 0.80) and 9% (13.04mm ± 1.28) in the strong category. The analysis data showed that each liquid soap variation in concentration of 3%, 6%, and 9% khalifa leaf extract had a significant difference ( p-value <0.05) in the results of the physical quality test and antibacterial activity. Conclusion: Based on the research results, it can be concluded that khalifa leaf extract with concentrations of FI (3%), F2 (6%), and F3 (9%) can be formulated into liquid soap that meets physical quality requirements and has antibacterial activity against Escherichia coli bacteria..   ABSTRAK   Meskipun sabun antibakteri mulai dikembangkan, penggunaan daun akalifa sebagai bahan aktif antibakteri pada liquid soap belum banyak dieksplorasi. Ekstrak daun akalifa (Acalypha wilkensiana Müell. Arg.) merupakan salah satu tanaman yang mempunyai aktivitas antibakteri terhadap bakteri Escherichia coli. Bakteri Escherichia coli ini penyebab diare yang paling umum dengan penyebaran melalui tangan yang kotor. Salah satu cara untuk mencegah penyakit karena bakteri adalah dengan menggunakan liquid soap yang dibuat menggunakan proses saponifikasi dengan atau tanpa penambahan bahan lain yang tidak mengiritasi kulit tangan. Tujuan: Tujuan penelitian ini untuk mengembangkan dan pemanfaatan ekstrak daun akalifa (Acalypha wilkensiana Müell. Arg.) menjadi liquid soap dengan berbagai variasi konsentrasi ekstrak. Penelitian ini dilakukan secara eksperimental laboratorium. Sampel daun akalifa diekstraksi menggunakan metode maserasi dengan pelarut etanol 70%, hasil ekstrak daun akalifa yang diperoleh dilakukan uji skrining fitokimia. Jumlah zat aktif yang digunakan dengan variasi konsentrasi FI (3%), F2 (6%) dan F3 (9%). Sediaan liquid soap yang dihasilkan dilakukan evaluasi mutu fisik meliputi organoleptis, homogenitas, pH, tinggi busa dan viskositas. Setelah itu uji aktivitas antibakteri menggunakan metode sumuran. Hasil penelitian menunjukan ekstrak daun akalifa mengandung senyawa alkaloid, flavonoid, tanin dan saponin. Hasil evaluasi mutu fisik ketiga formulasi liquid soap ekstrak daun akalifa memenuhi syarat rentang yang diperbolehkan oleh SNI. Hasil uji aktivitas antibakteri menunjukan bahwa semua formulasi menghasilkan daya hambat terhadap bakteri Escherichia coli, dengan diameter hambat konsentrasi 3% (7,55mm±0,61) kategori sedang dan konsentrasi 6% (10,94mm±0,80) dan 9% (13,04mm±1,28) kategori kuat. Data hasil analisis menunjukan masing-masing liquid soap variasi konsentrasi 3%, 6% dan 9% ekstrak daun akalifa memiliki perbedaan yang signifikan (p-value<0,05) terhadap hasil uji mutu fisik dan aktivitas antibakteri. Berdasarkan hasil penelitian dapat disimpulkan bahwa ekstrak daun akalifa dengan konsentrasi FI (3%), F2 (6%) dan F3 (9%) dapat diformulasikan menjadi liquid soap yang memenuhi persyaratan mutu fisik dan memiliki aktivitas antibakteri terhadap bakteri Escherichia coli.